Применение специализированных вычислителей на основе ПЛИС для решения задач информационной безопасности - Лобов, В. А.; Заворотна, М. Г. (ХНУРЕ, 2019)
Modern society can not be imagined in all spheres of human activity. Comprehensive implementation, on the one hand, noticeably helps in many work and everyday tasks. The introduction of new information technologies in the management and communications system is accompanied by the development and wide dissemination of new ways to ensure the security of information transmission and data protection. Formed two main areas in which in recent years, developing cryptographic tools to ensure secure transmission of information. The first is the improvement of traditional encryption systems. The second is the introduction of fundamentally new means of closing information.
Keywords: ПЛІС; інформаційна безпека; ЦОС